Remote Sensing Monitoring and Ecological Risk Assessment of Landscape Patterning in the Agro-Pastoral Ecotone of Northeast China - Min Guo; Shijun Wang (Complexity)
The agro-pastoral ecotone, an ecological transition zone connecting adjacent areas of agricultural planting area and grassland animal husbandry, has three features: a complex natural condition, relatively pronounced population pressure, and a fragile ecological environment. In this study, we conducted an ecosystem risk assessment in the western part of Jilin Province, China, based on multiscale and multitemporal remote sensing images and land-use data. Furthermore, we focused on land-use change from 1995 to 2015 by applying the dynamic change information survey method and carrying out a transfer track analysis. The results revealed three main findings. (1) The ecological risk index at the scale of 3 km × 3 km harbors significant spatial correlation. (2) The ecological risk index of unutilized land, forest land, and grassland is relatively high for each, and their anti-interference ability is weak, while the ecological risk index of construction land and water area is the lowest. (3) Human interference, e.g., construction activities and cultivated land occupation, is the leading factor driving the exacerbation of ecological risk and frequent land-use type conversions. At the study period’s end, a trend of slight contraction in the high-risk areas was found, indicating that land-use regulation and land protection policies have had significantly positive impact upon the lands’ ecological value. The overall study identified a reasonable research scale for eco-environmental risk assessment and discerned relationships between regional land-use changes through geospatial analysis. Moreover, our findings can help provide practical case study information applicable to similar regions with agro-pastoral ecotones.